Identifying wetland soil properties aiding the dormancy of Rift Valley fever vectors in central South Africa - Gqalaqha, Zikhona (University of the Free State, 2020)
Rift Valley fever (RVF) is a vector-borne zoonotic disease caused by the Rift Valley fever virus (RVFV). This virus is considered one of the largest emerging diseases in Africa and the Middle East, affecting public and livestock health and causing economic loss. RVF causes a high mortality rate in young animals and 100% abortion. The RVF outbreaks are triggered by favourable environmental and flooding conditions, which enable mosquitoes to proliferate and spread the virus. Although environmental factors such as soil, geology and vegetation play a crucial role in the maintenance and survival of the virus, the specifics of these environmental factors are still uncertain and therefore in dire need for more intensive research. Large epidemics are reported to occur in central South Africa. This study was conducted in the Free State and Northern Cape Provinces of South Africa. The study was initially conducted using 22 selected seasonal and temporary wetland sites (depressions/pans). Of those 22, 12 sites were classified as sites with mortalities and 10 sites were classified as sites without mortalities. The study was subsequently expanded to include eight (8) additional sites, all classified as sites without mortalities. Soil surveys were conducted: soil classification and soil samples were collected to besubjected to chemical, physical, biological and mineralogical laboratory analysis. Three analyses were per formed, which included descriptive analysis, non-parametric van der Waerden test and discriminant analyses. Soil water content was measured at selected sites using level loggers, EM 50, and watermark loggers. The results from the study indicated that only the cations (exchangeable Ca2+, K+, Mg2+, soluble Ca2+ and K+) of all chemical analyses indicated significant differences, with sites without mortalities having higher mean values than sites with mortalities. Coarse silt was the only physical property that differed significantly, with sites without mortalities recording higher mean silt content than sites with mortalities. Coarse silt has a lower water holding capacity than clay and can thus result in drier environments that do not favour mosquito eggs aestivation. Mortality sites and new sites without mortalities were characterised by soils that indicate longer periods of water saturation. This coincided with soil morphological indicators of water saturation, including low chroma colours, presence of mottles and concretions, and lime precipitation. Ni, Y, Zn and Ba were the only four elements that were found to be significantly different. Thefirst three elements are repo rted to be toxic and therefore might have suppressed the mosquito eggs aestivation in soils without mortalities. Conversely, Ba was high in the mortality sites. The microbial activity was inconsistent between the two years of sampling at all sites. The inconsistency was due to various reasons including vastly differing weather conditions between the two years, possible differing sampling methods and other unknown natural variations. The hatching of Aedes mosquito eggs is promoted by above-normal rainfall that results in flooding of wetlands and thus creates a conducive environment for hatching. In winter months, the hatching of mosquitoes is normally minimal due to lower rainfall, cold temperatures and windy conditions. In some sites, the abundance of mosquitoes was minimal even during flooding, due to 90% of mosquitoes hatching during the first inundation than subsequent flooding. The discriminant function previously developed was used to classify the (8) new sites without mortalities. Based on this classification, seven sites were erroneously classified as sites with mortalities, while only one site was correctly classified as a site without mortalities. A new discriminant function was subsequently developed using all available data. The identified RVF outbreak-prone areas coupled with mosquito surveillance and climate data can be used to develop RVF risk maps and thus contribute to the prevention and control of outbreaks. Future research needs to include the collection of Aedes mosquito to be tested for the virus, sampling should be expanded to other provinces as this allows for a larger sample to clearly define sites with mortalities and sites without mortalities.
Dissertation (M.Sc. (Soil, Crop and Climate Science))--University of the Free State, 2020
Keywords: Discriminant function; RVFV; Wetlands; Soil properties; Soil water saturation